2011
DOI: 10.1051/0004-6361/201117155
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating the Cepheid period-luminosity relation from the infrared surface brightness technique

Abstract: Aims. We determine period-luminosity relations for Milky Way Cepheids in the optical and near-IR bands. These relations can be used directly as reference for extra-galactic distance determination to Cepheid populations with solar metallicity, and they form the basis for a direct comparison with relations obtained in exactly the same manner for stars in the Magellanic Clouds, presented in an accompanying paper. In that paper we show that the metallicity effect is very small and consistent with a null effect, pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
204
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(232 citation statements)
references
References 328 publications
(513 reference statements)
24
204
4
Order By: Relevance
“…However, several researchers suggested that the p-factor actually does depend on the period of the pulsator (see e.g. Barnes 2009;Laney & Joner 2009;Storm et al 2011a;Nardetto et al 2014, and references therein), hence, for example, different p-factor values should be used for BL Her and W Wir stars. Given the uncertainties on the projection factor discussed above, in the following we will adopt the HST -based distance for κ Pav, and the zero point of the different P L, P W and P LC relations will be estimated including or not the BW-based distances for SW Tau and V533 Cen.…”
Section: Absolute Calibration Of P L P Lc and P W Relationsmentioning
confidence: 99%
“…However, several researchers suggested that the p-factor actually does depend on the period of the pulsator (see e.g. Barnes 2009;Laney & Joner 2009;Storm et al 2011a;Nardetto et al 2014, and references therein), hence, for example, different p-factor values should be used for BL Her and W Wir stars. Given the uncertainties on the projection factor discussed above, in the following we will adopt the HST -based distance for κ Pav, and the zero point of the different P L, P W and P LC relations will be estimated including or not the BW-based distances for SW Tau and V533 Cen.…”
Section: Absolute Calibration Of P L P Lc and P W Relationsmentioning
confidence: 99%
“…A well-sampled calibration featuring long-period Cepheids is desirable, as remote extragalactic Cepheids observed using HST/LBT typically exhibit periods greater than 10 days (Shappee & Stanek 2011;Gerke et al 2011), as their shorter-period counterparts are fainter. A well-sampled long-period cluster Cepheid calibration would likewise foster stronger constraints on the p-factor, which is used to establish IRSB distances (Gieren et al 2005b;Storm et al 2011;Ngeow et al 2012;Joner & Laney 2012;Neilson et al 2012b). A multi-object fiber-fed spectrograph can survey numerous stars surrounding long-period Cepheids, and automated methods can classify the resulting sample and establish spectroscopic parallaxes (Manteiga et al 2009;Mugnes & Robert 2013).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…The fourth case is the LMC+HST period-projection factor relation from Storm et al (2011a,b), though we could also include results from Mérand et al (2005), Groenewegen (2007) and Ngeow et al (2012). The LMC+HST Pp relation from Storm et al (2011a) has a slope measured from LMC Cepheids while the zero-point is measured from Galactic Cepheids. Our results appear to agree with the Nardetto et al (2009) relation, but not the observed relation, verifying that limb-darkening does not explain the difference between the observed and theoretical relations, hence we must consider different phenomena to explain the difference between the relations from Nardetto et al (2009) and Storm et al (2011a).…”
Section: Period-projection Factor Relationmentioning
confidence: 99%
“…Storm et al (2011b) found similar results for LMC Cepheids, also using the infrared surface brightness technique, for different observations. Furthermore, Storm et al (2011a) used observations of Galactic Cepheids with known HST parallaxes to verify the steeper period dependence of the projection factor; we refer to this type of analysis as the LMC-HST Pp relation and p-factor. Mérand et al (2005) and Groenewegen (2007) measured the p-factor for Galactic Cepheids with known distances using interferometric and spectroscopic observations, both authors measured p = 1.27.…”
Section: Introductionmentioning
confidence: 99%